Effects of Chromolaena odorata leaves as amendments to poultry manure and inorganic fertilizer to improve growth, yield, biomass accumulation and inorganic content of tomato (Lycopersicum esculentum). - Balinas, Chona Mae
Chromolaena odorata (a weed in the family Asteraceae) has been shown to enhance the buildup of organic matter in fallow system in tropical soil. Therefore, the aim of this study was to determine the effects of Chromolaena odorata leaves as an amendment to poultry manure and triple 14 inorganic fertilizer on the growth, yield, biomass accumulation and inorganic contents of Lycopersicum esculentum. The field experiment was conducted at Agsanayan Buenavista Guimaras where the weed has wide distribution. The leaves of C. odorata were aired dried and composted using Berkeley method. the compost obtained was used as an amendment to ethier poultry manure and inorganic fertilizer and was tested on tomato for three months in RCBD. Obtained results proved that tested treatments with amendments of C. odorata were significantly higher in lengths of shoots and roots, flower and fruit yield, amount of biomass accumulated and inorganic contents of tomato than those with no amendments of C. odorata. Therefore, C. odorata is an efficient amendments to both organic and inorganic fertilizers. It was suggested that the weed should be utilized to serve as a green manure.